Synchronous multiple carcinoma with small intestine and pulmonary neuroendocrine involvement: A case report. Issue 45 (November 2017) - Shan, Binbin; Zhang, Quanmao; Li, Yuan; Han, Fucai
Abstract: Rationale: In clinical work, neuroendocrine synchronous multiplicity carcinoma was relatively rare. Most were confirmed by the pathological diagnosis of a certain part of the body combined with the imaging of the whole body, while cases that had both pathological and immunohistochemistry diagnosis were few. Patient concerns: A patient who presented with abdominal pain visited our hospital, and was diagnosed with lesions in both the small intestine and lung. Diagnoses: Both were considered primary tumors by imaging, and diagnosed as neuroendocrine carcinomas by pathology. Interventions: The intestinal lesion was surgically resected, and the lung tumor treated by chemoradiotherapy. Outcomes: The survival time of this patient exceeded 24 months. Lessons: The diagnosis relied on clinical, imaging, pathological, and immunohistochemical features, which confirmed a synchronous multiple carcinoma. Treatment was based on the pathological types. Through this case report, the clinical and pathological data of neuroendocrine synchronous multiplicity carcinoma could be enriched.